If p + q = 1 , evaluate r = 0 ∑ n r 2 ( r n ) p r q n − r
Take n = 1 1 , p = 0 . 3 4
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There are 2 ways to "get rid" of the r term. One way is to integrate / differentiate it, and the other is to use the relation that ( r n ) = r n ( r − 1 n − 1 ) .
@Calvin Lin sir, that was method 2, which I did not mention... Thanks!
Log in to reply
Well, you actually used both ways in this method, so I was pointing out how to make the r 2 disappear. It would be nice if you added an approach which only used one of these ways (twice) to obtain the answer.
Log in to reply
It's like in this method,I was able to remove one r, so I used diffentiation to remove the next one... I'll post the other way today. Thanks!
Log in to reply
@Kishore S. Shenoy – RIght, so the way to use the same approach, is to consider ∑ ( r 2 − r ) ( r n ) p r q n − r and then ∑ r ( r n ) p r q n − r and sum the two of them.
Log in to reply
@Calvin Lin – Yes this same method... Method 2
If the random variable X has the Binomial distribution B ( n , p ) , we are asked to calculate E [ X 2 ] = V a r [ X ] + E [ X ] 2 . It is standard bookwork that X has mean n p and variance n p q , and so our answer is n p q + n 2 p 2 . For the given values of n , p , this makes the answer 1 2 5 2 0 5 7 = 1 6 . 4 5 6 .
To show that the binomial distribution has the stated mean and variance, note that if X ∼ B ( n , p ) , then X = Z 1 + Z 2 + ⋯ + Z n , where Z j is equal to 1 if the j th trial is a success, and 0 otherwise. Then Z 1 , Z 2 , … , Z n are independent and identically distributed, and E [ Z 1 2 ] = E [ Z 1 ] = P [ Z 1 = 1 ] = p so that E [ Z 1 ] = p V a r [ Z 1 ] = p − p 2 = p q Thus E [ X ] V a r [ X ] = j = 1 ∑ n E [ Z j ] = n p = j = 1 ∑ n V a r [ Z j ] = n p q
Problem Loading...
Note Loading...
Set Loading...
Method 1
r = 0 ∑ n r 2 ( r n ) p r q n − r = r = 0 ∑ n n p ( r − 1 n − 1 ) r p r − 1 q n − r = n p r = 0 ∑ n d p d ( ( r − 1 n − 1 ) p r q n − r ) = n p d p d [ p ( p + q ) n − 1 ] = n p [ ( p + q ) n − 1 + ( n − 1 ) p ( p + q ) n − 2 ] = n p + n ( n − 1 ) p 2
∴ r = 0 ∑ n r 2 ( r n ) p r q n − r = n p + n ( n − 1 ) p 2